PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA (PERIODE 2015-2017) - Elda Prastiwi; Maslichah Maslichah (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT This study aims to: 1) Know the effect of Good Corporate Governance which includes Managerial Ownership, Board of Commissioners, Board of Directors, Audit Committee and Return on Equity (ROE) on Stock Prices. 2) Knowing the effect of Good Corporate Governance in aspects of Managerial Ownership influences the Stock Price. 3) Knowing the effect of Good Corporate Governance in aspects of the Board of Commissioners has an effect on Stock Prices. 4) Knowing the effect of Good Corporate Governance in aspects of the Board of Directors influences the Share Price. 5) Knowing the effect of Good Corporate Governance in the aspects of the Audit Committee has an effect on Stock Prices. 6) Knowing the effect of Return on Equity (ROE) on Stock Prices. While the sample in this study is a manufacturing company listed on the Indonesia Stock Exchange. The sampling technique uses a purposive sampling method. The research sample was 29 companies that met the characteristics. Data analysis using multiple linear regression. The results of this study indicate that 1) Managerial Ownership, Board of Commissioners, Board of Directors, Audit Committee, Return On Equity simultaneously have a significant effect on stock prices. 2) Managerial ownership does not have a significant influence on stock prices. 3) The board of commissioners does not have a significant influence on stock prices. 4) The board of directors has a significant influence on the variable share price. 5) The audit committee does not have a significant influence on the stock price variable. 6) Return on equity (ROE) has a significant effect on variable stock prices. The results of this study are expected to be a reference for further research and a consideration for the company, especially regarding Good Corporate Governance and Return On Equity in increasing stock prices.Keywords: Managerial Ownership, Board of Commissioners, Board of Directors, Audit Committee, Return On Equity, and Stock Prices.